REPARATIVE CHONDROGENESIS AT RATS SHINBONE PROXIMAL EPIPHYPHIS TRAUMATIC INJURY WITH THE USE OF WARTON DRUGS STAR CELLS MEZENCHENICHEMIS IN THE EXPERIMENT - Fishchenko, V.O.; Gavrilyuk, A.O.; Rosha, L.G.; Botsul, O.V.; Bevz, V.O.; Sukhan, D.S.; Koreneva, G.B. (World of Medicine and Biology, 2021)
The purpose of the study was to perform a comparative morphological study of damaged cartilage tissues in the conditions of applying mesenchymal stem cells of Wharton's jelly and without them. Experimental studies have confirmed the positive effect of mesenchymal stem cells of Wharton's jelly to restore the structure and function of articular cartilage after experimental traumatic injury. The results of morphological studies indicate the acceleration of reparative osteochondrogenesis with the use of mesenchymal stem cells for 1.5-2 weeks than in the control group. The influence of mesenchymal stem cells on the formation of structured timely osteogenesis without the formation of excessive early production of the ossifying matrix and dystrophic changes of chondrocytes and chondroblasts is proved. The authors argue that the results of the study pave the way for an effective and safe method of cellular regenerative medicine of the musculoskeletal system.
Keywords: experimental joint trauma; morphological disorders; mesenchymal stem cells; regenerative medicine; Wharton's jelly